EP.TU.380Compliance with delirium guidelines in older surgical patients and susceptibility to improvement. (28th October 2021) - Toe, Ko Ko Zayar; Pressler, Marc; Lees, Nick; Vardy, Emma; Price, Angeline
Abstract: Aim: Delirium in older hospitalised adults is both common and serious, particularly following surgery. It is associated with increased mortality, prolonged admission and greater care needs. All patients ≥ 65 years should have a delirium assessment within 24 hours of admission, and again post-operatively. Where delirium is identified, a thorough assessment of reversible causes should be undertaken using validated tools. Despite clear guidelines, delirium remains under-recognised and inconsistently managed. A study was undertaken to determine compliance with delirium assessment and management guidelines for older surgical patients in one acute hospital, and their susceptibility to improvement. Methods: A QI project was undertaken using the PDSA cycle. 50 patient records were reviewed retrospectively. Multidisciplinary educational sessions were delivered. A further 50 patient records were audited after 1 month. Primary outcome: delirium assessment (4AT) within 24 hours of admission. Secondary outcome: TIME bundle completed where delirium identified. Results: 72% (36/50) of patients had a 4AT pre-intervention → 84% (42/50) post-intervention. Assessments within 24 hours were 56% and 77%, respectively. 8% (4/50) were diagnosed with delirium pre-intervention → 14% (7/50) post-intervention. Most delirium cases occurred post-operatively (7/11). Despite increased assessment and detection, compliance with the TIME bundle did not improve (2/4 vs 2/7). Conclusion: Delirium assessment and identification is improved through the use of a standard tool (4AT) and targeted educational sessions. As a common post-operative complication, delirium assessment is an important aspect of routine post-operative care. Further work is needed to improve compliance with use of the TIME bundle when delirium is present.